Evaluation of technical and economic efficiency of cement production - E. V. Zaytseva (Publishing House of the State University of Management, 2019)
The main indicators-indicators, that are involved in the integrated assessment for comparison and ranking of cement enterprises for technical and economic efficiency, have been considered and analyzed. This assessment serves as the basis for strategic decisions on the development of technological systems of cement production. Formation and filling of evaluation matrices of the level ofproduction and economic and financial potentials of cement production was carried out with the help of structural and logical analysis of the inherent strengths and weaknesses. The presented estimates reflect all the main areas of activity of cement enterprises in technological and economic aspects.